The relationship between workload and work stres with work accidents on technicians in the Batam Center sector at PT.Telkom access in 2022 - SISKA, SISKA DELVIA; Dr.Krismadies; leni utami (Fakultas Ilmu Kesehatan, Universitas Ibnu Sina, 2023)
This study aims to determine the relationship between workload and work stres with work accidents on technicians in the Batam Center sector at PT.Telkom access in 2022. The research methodology is quantitative analytic with a cross sectional design approach. The population in this study were workers at PT. Telkom access in 2022. The sampling technique used the total sampling method with the number of respondents being 50 trouble technician workers and using the chi square test, with a questionnaire research instrument. The results of the study found that there was a relationship between workload and work accidents with a value (p value = 0.002) the relationship between work stres and the incidence of work accidents with a value (p value = 0.005) which means there is a significant relationship. It is concluded that all these variables are related where <a = 0.05 which means Ho is rejected. It is recommended that companies need to pay attention to the workload of employees and work stres and supervise workers to prevent work accidents.